2006
DOI: 10.1088/0957-0233/17/7/013
|View full text |Cite
|
Sign up to set email alerts
|

Ridge-waveguide-based polarization insensitive Bragg grating refractometer

Abstract: A highly sensitive waveguide Bragg grating (WBG) sensor for measuring small changes of the refractive index of the surrounding liquid is presented. By using an open top ridge waveguide with a small core, the evanescent field interaction of the guided mode with the liquid analyte on the top of the waveguide is enhanced. The sensitivity measured via a shift in the resonance wavelength of the Bragg grating as high as 1 pm of wavelength shift for a change of 4 × 10−5 in the refractive index around 1.402 is realize… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 12 publications
(20 reference statements)
2
20
0
Order By: Relevance
“…A strong Bragg grating with index modulation was induced in the hydrogen loaded m m waveguide with 40 Hz, 100 mJ/cm pulse of polarized UV irradiation (oriented normal to the waveguide axis). The laser beam was polarized to reduce the birefringence of the device [10]. The total UV exposure for the fabrication of the Bragg grating with 21 dB transmission and 0.7 nm bandwidth is 1 kJ/cm .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…A strong Bragg grating with index modulation was induced in the hydrogen loaded m m waveguide with 40 Hz, 100 mJ/cm pulse of polarized UV irradiation (oriented normal to the waveguide axis). The laser beam was polarized to reduce the birefringence of the device [10]. The total UV exposure for the fabrication of the Bragg grating with 21 dB transmission and 0.7 nm bandwidth is 1 kJ/cm .…”
Section: Resultsmentioning
confidence: 99%
“…It is shown that the sensitivity to the analyte increased with decreasing waveguide core width. As the sensitivity is defined as , it is dominated by the change of the core mode evanescent sensitivity that increases with decreasing core width [10]. The small core size m m device had the highest sensitivity.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In waveguide structures, the resonant wavelengths of fundamental harmonic backward and forward propagating modes may be written as [1][2][3][4]:…”
Section: Analysesmentioning
confidence: 99%